Single CCA for IEEE 802.15.4 networks: a cross layer energy model. Issue 3 (1st May 2019) - Biswas, Sankalita; Dhar Roy, Sanjay; Chandra, Aniruddha
Abstract : For data frame transmissions in beacon‐enabled mode, an IEEE 802.15.4 node performs two consecutive clear channel assessments (CCAs) to sense the channel after back off. Here, the authors study what would happen if the medium access control (MAC) layer performs only one CCA instead. Although it is apparent that the frame transmission cycle would be shortened with single CCA, it is not straightforward to assess the effect of single CCA on the overall transmission energy. A Markov chain‐based MAC operation model is therefore constructed to analyse single‐CCA‐based MAC layer parameters. A combined physical (PHY) and MAC layer energy model is formulated next. It was found that the single CCA‐based MAC outperforms its standard double CCA‐based counterpart from the energy efficiency perspective.